2018
DOI: 10.1155/2018/5421961
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis Index in Acromegaly: Correlation with Insulin Resistance Regardless of the Disease Control

Abstract: Objective In acromegaly, both lipotoxicity secondary to GH excess and insulin resistance have a significant impact on the liver. Ultrasonography has shown poor sensitivity in detecting hepatic steatosis and noninvasive methods have been proposed. We evaluated the hepatic steatosis index (HSI), a validated surrogate index of hepatic steatosis, and we correlated it with disease activity and insulin resistance. Design Thirty-one patients with newly diagnosed acromegaly were studied at diagnosis and after 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…It is unknown whether acromegaly predisposes or prevents hepatic accumulation of fat since the pathophysiological network regulation is complex and not fully understood [48,49]. Among a sample of 19 newly diagnosed ACRO, Ciresi et al reported that 61.0% had hepatic steatosis, with no improvement after 12 months of therapy with octreotide (control of the disease was reached in 58%) [50]. Conversely, they reported a significant improvement in the hepatic steatosis index with therapy (p < 0.001) [50].…”
Section: Livermentioning
confidence: 99%
“…It is unknown whether acromegaly predisposes or prevents hepatic accumulation of fat since the pathophysiological network regulation is complex and not fully understood [48,49]. Among a sample of 19 newly diagnosed ACRO, Ciresi et al reported that 61.0% had hepatic steatosis, with no improvement after 12 months of therapy with octreotide (control of the disease was reached in 58%) [50]. Conversely, they reported a significant improvement in the hepatic steatosis index with therapy (p < 0.001) [50].…”
Section: Livermentioning
confidence: 99%
“…23,24 Moreover, low serum IGF-1 concentrations have also been associated with NAFLD and it has been suggested that hepatic insulin resistance modulates hepatic GH production and thus IGF-1 concentrations. 20 The observed risk with GH and IGF-1 deficiencies would imply that treated patients with acromegaly might be prone to develop NAFLD, because treatment does, in some cases, lead to the development of GH deficiency, as illustrated in a recently published case study. 20 The observed risk with GH and IGF-1 deficiencies would imply that treated patients with acromegaly might be prone to develop NAFLD, because treatment does, in some cases, lead to the development of GH deficiency, as illustrated in a recently published case study.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 A recent study showed hepatic steatosis (as assessed by a surrogate marker, the hepatic steatosis index) to be related to insulin resistance and the reduction of IGF-1 and GH levels; after 12 months of follow-up, improvements to insulin sensitivity paralleled reductions of hepatic steatosis. 20 The observed risk with GH and IGF-1 deficiencies would imply that treated patients with acromegaly might be prone to develop NAFLD, because treatment does, in some cases, lead to the development of GH deficiency, as illustrated in a recently published case study. 27 Moreover, an intervention study and another case study both report histological NASH resolution upon GH correction in patients with GH deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations